Relationships Between Calling and Academic Motivation in Post-Secondary Students - Woitowicz, Lyndsay A.; Domene, José F. (Canadian Journal of Counselling and Psychotherapy, 2013)
The relationships between academic motivation and of sense of calling, gender, type of career aspiration and religious affiliation were examined in a sample of post-secondary students. Data were collected from a sample of 368 students, using an online survey. Results of hierarchical multiple regressions revealed that, after the effects of key individual characteristics were controlled for, the two dimensions of calling were small but significant predictors of academic motivation.  Specifically, each dimension of calling uniquely related to both intrinsic motivation and extrinsic motivation, while solely having a calling was related to amotivation. Additionally, a significant calling by religious affiliation interaction effect emerged for intrinsic motivation, as well as a significant calling by type of career aspiration interaction for amotivation. Results suggest that calling and its interactions with other key variables are important to consider in understanding the academic motivation of post-secondary students.